Assessment of the nutritional safety of new potatoes imported to Poland using an ascorbate-nitrate index - Wadas Wanda; Raczuk Jolanta (National Institute of Public Health - National Institute of Hygiene, 2018)
Background: New potatoes are imported to Poland mainly from the Mediterranean countries. In climate of the Mediterranean Basin potatoes can be grown twice a year. The different environment conditions during plant growth have effect on the tuber quality. Objective: The aim of the study was to assess the nutrition safety of new potatoes imported to Poland in the winter period from Mediterranean countries on the basis of the ascorbate-nitrate index. Material and methods: The study material included potatoes imported from Cyprus, Egypt and Israel, purchased in the Siedlce city, from the beginning of February to the end of March 2015. Laboratory tests were performed on a total of 54 potato samples. The contents of L-ascorbic acid was determined by titration method with the 2,6-dichlorophenolindophenol according to Tillmans and nitrate by spectrophotometric method based on the Griess reaction. The ascorbate-nitrate index (IAN) as the ratio of L-ascorbic acid amount-to-nitrate amount in potato tubers was calculated. Results: The L-ascorbic acid content in imported new potatoes ranged from 102.7 to 131.0 mg kg-1 and nitrate content from 22.70 to 64.74 mg N-NO3 kg-1 of the fresh weight of tubers. The L-ascorbic acid content in potatoes imported from Cyprus was similar to potatoes of the same cultivar imported from Egypt. The L-ascorbic acid content in potatoes imported from Israel was at a similar or higher level than in potatoes originating from Cyprus or Egypt. The lowest nitrate were in potatoes imported from Egypt. The nitrate content determined in potatoes imported from Cyprus was almost 2.5-times higher than for potatoes of the same cultivar imported from Egypt, whereas the nitrate contents in potatoes imported from Israel was 1.6-2-times higher than in potatoes originating from Egypt. The IAN was from 1.68 to 5.73. The IAN for the potatoes imported from Egypt was above 2.5-times higher than for potatoes of the same cultivar imported from Cyprus, and almost 2-times higher than for potatoes imported from Israel. Conclusion: The nitrate content in tested potato samples did not exceed the permissible content of 200 mg NO3 kg-1 of the fresh weight of tubers. The IAN value calculated for all tested potato samples was higher than 1, which indicates that new potatoes imported to Poland in the winter period from Mediterranean countries are safe for human health regarding the nitrate content.